No return: Jews, Christian usurers, and the spread of mass expulsion in medieval Europe - Dorin, Rowan (Histories of economic life, 2023)
Introduction -- Expulsion, Jews, and Usury: Trajectories of Christian Thought and Practice -- Inventing Expulsion in England, 1154-1272 -- Inventing Expulsion in France, 1144-1270 -- Canonizing Expulsion: The Second Council of Lyon, 1274 -- Disseminating Expulsion: Synods, Summas, and Sermons -- Emulating Expulsion: England and France, 1274-1306 -- Ignoring Expulsion: Episcopal Evasion and Papal Inaction, 1274-1400 -- Expanding (and Impeding) Expulsion: Jews, Usury, and Canon Law, 1300-1492 -- Conclusion.